Time-frequency signature investigation of operational shock-induced slider transient dynamics and damage by enhanced ensemble noise-reconstructed EMD. (October 2019) - Wang, Yu; Yuan, Jing; Yang, Ang; Chen, Shaowen
Abstract: A continuous increase of the storage density of a hard disk drive (HDD), e.g., currently 1 Tb/in 2, requires the physical clearance between magnetic head and disk to be reduced to angstrom level. At such ultra-thin clearance, a sudden shock occurred in HDD may destroy the head-disk interface caused by the unexpected impacts. The damage mechanisms involving in the operational shock testing and its dynamic analysis are crucial, which are few studied previously. Moreover, the meaningful interpretation to the slider/disk interactions is challenging to be addressed due to the weak local nonstationary dynamic characteristics contaminated by heavy noise. To reveal the damage mechanisms, this paper designed and conducted the experimental studies of shock-induced slider-disk interactions, and proposed enhanced ensemble noise-reconstructed empirical mode decomposition (EMD) based time-frequency method to identify the shock-induced slider transient dynamics. Hereinto, the neighboring coefficient denoising and minimax threshold are developed to enhance the weak shock-related signatures. Meanwhile, two kinds of time-frequency signature indicators are introduced to respectively describe the damage of one sudden shock and that of the whole shock process. The results show that the method can successfully identify the main modes of slider-disk interactions during shocking process and evaluate the damage degree, well agreed with the slider damage inspected by scanning electron microscope (SEM). Highlights: An in-situ monitoring technology for slider dynamics during shock process is presented. Enhanced ensemble noise-reconstructed EMD method is proposed to reveal the shock-induced slider dynamics. Two kinds of time-frequency signature indicators are introduced to quantitatively identify of the shock-induced damages. The shock tests are used to validate the performance of the method for different degree of shock-induced damages.